2022
DOI: 10.1038/s41598-022-13222-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variables and genome-environment interactions predicting IBD diagnosis in large UK cohort

Abstract: A combination of genetic susceptibility and environmental exposure is thought to cause inflammatory bowel disease (IBD), but the non-genetic component remains poorly characterized. We therefore undertook a search for environmental variables and gene-environment interactions associated with future IBD diagnosis in a large UK cohort. Using self-report and electronic health records, we identified 1946 Crohn’s disease (CD) and 3715 ulcerative colitis (UC) patients after quality control in the UK Biobank. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…CD can affect any portion of the gastrointestinal tract with inflammation that can span across all layers of the gut, while UC is localized to the colon and rectum and confined to the mucosa. IBD is believed to be driven from the complex interplay between environmental factors and genetic susceptibilities, resulting in dysregulated immune responses to environmental triggers and the breakdown of the epithelial barrier and intestinal homeostasis (Torres et al, 2017; Van Heel et al, 2001; Yang and Jostins-Dean, 2022). Genome-wide association studies have revealed more than 200 IBD-susceptiblility genes, which are involved in microbial sensing, antigen presentation, autophagy, T-cell signaling, and other immune-related pathways (de Lange et al, 2017; Jostins et al, 2012; Liu et al, 2015; Momozawa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…CD can affect any portion of the gastrointestinal tract with inflammation that can span across all layers of the gut, while UC is localized to the colon and rectum and confined to the mucosa. IBD is believed to be driven from the complex interplay between environmental factors and genetic susceptibilities, resulting in dysregulated immune responses to environmental triggers and the breakdown of the epithelial barrier and intestinal homeostasis (Torres et al, 2017; Van Heel et al, 2001; Yang and Jostins-Dean, 2022). Genome-wide association studies have revealed more than 200 IBD-susceptiblility genes, which are involved in microbial sensing, antigen presentation, autophagy, T-cell signaling, and other immune-related pathways (de Lange et al, 2017; Jostins et al, 2012; Liu et al, 2015; Momozawa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…IBD is a chronic inflammatory disorder of the gastrointestinal tract that is caused by genetic susceptibility and environmental factors [ 35 , 36 , 37 ]. It is generally categorized into two subtypes, Crohn’s disease (CD) and ulcerative colitis (UC), based on clinical pathological features.…”
Section: Etiopathogenesis Of Inflammatory Bowel Diseases (Ibd)mentioning
confidence: 99%
“…Patients with increased genetic risk for IBD but healthy lifestyles had a lower risk of developing IBD than those with increased genetic risk and unhealthy lifestyles (HR: 2.23 vs 4.40)[ 25 ]. Yang and Jostins-Dean[ 26 ] published data using the information of IBD patients from a United Kingdom biobank. They analyzed 24 dietary exposures, perinatal childhood exposures, and lifestyle factors in individuals.…”
Section: Epigenomicsmentioning
confidence: 99%
“…They showed that multiple factors interacted, causing polygenic risk in predicting IBD occurrence. Factors such as appendectomy, smoking, childhood antibiotic use, exposure to the sun in winter, socioeconomic factors, and oral contraceptive use played a role in IBD pathogenesis[ 26 ]. Ryan et al [ 27 ] found that inflamed and non-inflamed colonic mucosa in IBD patients had different microbiota composition and epigenetic profiles.…”
Section: Epigenomicsmentioning
confidence: 99%